(untitled) (Revista Brasileira Multidisciplinar, 2026)
The emergence of the SARS-CoV-2 virus significantly impacted dental practice, including education in dental school clinics of higher education institutions. Several preventive measures were indicated to minimize the risks of cross-infection during dental care and must be strictly followed to prevent such infections. The present study aimed to evaluate the level of contamination of face shields by SARS-CoV-2 in the dental school clinic of a public university, through the analysis of inanimate surfaces. This is a prospective observational study, composed of a convenience sample. Samples were collected from the external surfaces of 230 face shields used by students and professors after clinical dental care, using cotton swabs. The samples were stored in sterile physiological saline solution, transported, and processed according to the research laboratories’ guidelines. Gene expression analysis was performed using Real-Time Polymerase Chain Reaction (RT-PCR) following the manufacturer’s instructions. All samples tested negative for SARS-CoV-2 detection. Based on the results, it can be concluded that by following strict biosafety protocols, in-person practical activities are safe.